(untitled) (Eurasian Medical Research Periodical, 2023)
To date, a number of techniques and anti-spay coatings have been developed and successfully used in experimental studies. Their role is to activate fibrinolysis, impede coagulation, reduce the inflammatory response, inhibit collagen synthesis or create a barrier between adjacent wound surfaces[1]. It is well known that some basic surgical principles should be followed in all abdominal surgeries. Damage to the peritoneum should be avoided by careful tissue handling, careful hemostasis, continuous irrigation and avoiding unnecessary drying, ineffective use of foreign bodies and suturing or tissue clamping